Effect of pH on Structure and Green Emission of Er/Yb/Mo Tri-doped Hydroxyapatite - Van, Hoang Nhu; Dung, Nguyen Tien; Hai, Nguyen Van; Thai, Cu Van; Minh, Vu Thi Ngoc; Truong, Nguyen Xuan; Hoan, Bui Thi; Huan, Pham Van; Vuong, Pham Hung (VNU Journal of Science: Mathematics - Physics, 2022)
This paper reported the impact of pH on the structure, morphology, and the green upconversion (UC) emission of Er/Yb/Mo tri-doped hydroxyapatite (HA) synthesized through hydrothermal method. X-ray diffraction confirmed that the pH of the solution strongly influenced the phase composition of the phosphors, and HA single phase was obtained at a high pH value. Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) images of the phosphor exhibited rod-like morphology, and their length increased with increased of the pH values. Under laser-diode excitation wavelength of 975 nm, the phosphor showed typical upconversion emission bands of the  ion: strong green emission bands around 510-535/540-560 nm and weak red emission bands around 630-680 nm. The green and red emission intensity as a function of pH reached its maximum value at pH8. Finally, the emission intensity of